Unified Autostress Method - Schilling, Charles G. (Engineering Journal, 1991)
A new unified method of inelastic analysis that can be applied in both the AASHTO overload and maximum load checks is developed in this paper. Formerly, different methods of analysis were used in these two checks in the AASHTO alternate load factor design procedures. The new method, which is called the Unified Autostress Method, can account for yielding at any number of negative- and positivebending locations, such as pier and flange-transition locations. The new method is founded on classical indeterminate theory and can be readily adapted for computer programming.In continuous spans, automoments are caused by yielding at various locations and remain after the loading is removed. These automoments are calculated by satisfying a continuity relationship at all pier locations and a rotation relationship at all yield locations. The continuity relationship depends on the stiffness properties along the entire length of the member, and the rotation relationship depends on the properties of the cross sections at the yield locations. An iteration procedure is required for more than two spans; one such procedure, which has been shown to work satisfactorily, is outlined.